2000
DOI: 10.1063/1.1150220
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a piezoelectric tuning fork/optical fiber assembly in a near-field scanning optical microscope

Abstract: Articles you may be interested inSensitivity maximized near-field scanning optical microscope with dithering sample stage Rev. Sci. Instrum. 83, 093710 (2012); 10.1063/1.4754290 Double-resonance probe for near-field scanning optical microscopy Rev. Sci. Instrum. 77, 033703 (2006); 10.1063/1.2186386 Q -factor optimization of a tuning-fork/fiber sensor for shear-force detection Appl. Phys. Lett. 86, 064103 (2005); 10.1063/1.1861983 Apertureless near-field scanning optical microscope based on a quartz tuning fork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…The high-resolution imaging of SNOM is achieved when the probe-sample separation is precisely controlled in the near-field regime. Therefore, various distance regulation schemes have been proposed, such as electron tunneling [ 2 ], frustrated total internal reflection [ 13 ], background fluorescence increases [ 14 ], and the shear-force control schemes [ 15 , 16 ], which are now widely used owing to their simplicity, compactness, reduced drift in the feedback loop, and lower levels of the parasitic optical background [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high-resolution imaging of SNOM is achieved when the probe-sample separation is precisely controlled in the near-field regime. Therefore, various distance regulation schemes have been proposed, such as electron tunneling [ 2 ], frustrated total internal reflection [ 13 ], background fluorescence increases [ 14 ], and the shear-force control schemes [ 15 , 16 ], which are now widely used owing to their simplicity, compactness, reduced drift in the feedback loop, and lower levels of the parasitic optical background [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, researchers adopted the single degree of freedom vibration theory or the Euler–Bernoulli beam theory to analyze the dynamic behavior of the TF-probe [ 17 , 22 , 23 ], and concluded that the shear force mechanism was induced by the lateral interaction between the probe and the sample. Meanwhile, various experiments have also been implemented to investigate the shear force mechanism of the TF-probe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the optical detection method, tuning fork probe–sample distance regulation has a number of advantages, including simplicity, compactness and lack of parasitic optical background. However, the preparation of a tuning fork – fibre tip assembly with reproducible characteristics is not an easy task (Shelimov et al ., 2000). Here we propose an alternative, a tapping‐mode force sensing method based on the use of a piezoelectric bimorph cantilever (Shang et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…G; ";öB ê2ö «Ò~º ~ Þ 7çº TM ãÖ ;~&. ò R" ö Ò~ ÒBÚöº >; êÿ ¶¢ Ï shear force feedback O» [11][12][13] 'Ï>î. ö B ÒÏB ò~ Nº 2 µm Ú ¢>' NSOMG; …”
unclassified